EFFECTS OF SOME INSECTICIDES ON DISPERSAL BEHAVIOR OF TETRANYCHUS MEXICANUS (ACARI: TETRANICHIDAE) AND OBSERVATIONS ON IT’S CONTROL WITH SOME ACARICIDES - HERNÁNDEZ-E., NORBERTO; VARGAS, HÉCTOR A.; ZULUAGA, JOSÉ IVAN (Revista Colombiana de Entomología, 1988)
The effect of ometoate, dichlorvos and decametrin on dispersal behavior of T. mexicanus was studied under meshing house conditions, with an average temperature of 24°C and 70,6% R.H. Likewise observations of chemical control of the some species were made with products such as binapacril, triazophos, propargite and sulphor. Several answers to the dispersal behavior of T. mexicanus were found according to the park on which products were applied. Decametrin is an insecticide that causes repellence of T. mexicanus but only when it’s directly in contact with the mite, thus it causes dispersal of tetraniquids from treated areas to others free of the treatment. Ometoate and dichlorvos did not produce dispersal. Within chemical control, triazophos show higher efficiency against T. mexicanus.